(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The family and kinship culture, which includes traditional associations, is based on a strong foundation in Turkic society. Nowadays, many research works in the field of language and culture, especially related to customs and traditions, are based on the disclosure of national understanding and national style of life in Turkic world. Nevertheless, as a linguicultural fact, there is not enough research in Turkish proverbs in the literature of our country. This article analyses the characteristic features of the tradition «dünürlük» of Turkish people in the context of all-Turkish traditions based on sustainable terms related to the tradition of swattering. The purpose of this article is to reveal the meaning of the tradition «dünürlük» in the Turkish sense and, with the help of a content-thematic grouping, to identify the specificity of Turkish sustainable terms, which reflect the tradition of swattering. The article gives examples of sustainable terms, their translation and meaning, which make it possible to determine the relevance and prerequisites of the tradition «dünürlük». Based on the analysis of the material, the Turkish sustainable terms are compared in linguoculturological aspect. Key words: «dünürlük», Turks, traditions, expressions, linguoculture.